The 2006 Federal Budget: A Gender Analysis of the Superannuation Taxation Concessions - Austen, S; Sharp, R (My University, 2007)
Gender analyses of Australia’s retirement incomes policy have consistently pointed to large inequalities in the benefits received by men and women. These findings are in accordance with feminist theory, which generally identifies how gender impacts of policy measures can arise from the fact that men and women systematically occupy different economic and social positions. This paper provides new information on the gender impacts of Australia’s retirement incomes policy by examining the distributional impacts of changes in superannuation tax concessions announced in the 2006 federal budget. This information indicates that the budgetary changes provided substantial taxpayer-funded benefits to individuals who occupy the economic and social positions typically associated with men, whilst they pose additional risks to the retirement incomes of many women.
Vol. 10, No. 2, June 2007, pp 61 - 77
Keywords: Gender -- Gender differences; Employment -- Exit from employment (Retirement/Redundancy); Policy; Income & Finance -- Income inequality; Ageing -- Retirement; Ageing; Labour market; Income, wealth and finances; Income & Finance; Policy; Employment; Ageing; Gender; Income inequality; Gender differences; Retirement; Exit from employment (Retirement/Redundancy); Employment and unemployment; Ageing; Income, wealth and finances